Рsychological characteristics of dynamic value-semantic orientations of cadets in the socialization process - Vasilyev, S.; Andruschenko, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
Psychological peculiarities of value orientations dynamics as well as the dynamics of semantic orientations are described in the process of socialization while studying at a higher educational institution. The determination of priorities as a result of both value and semantic spheres reflection and an indicator of maturity level of an individual is actualized.